Kapabilitas Dynamic Governance Dalam Pembangunan Zona Integritas Pada Kantor Pelayanan Perbendaharaan Negara - Rizki, Muhammad; Sujianto, Sujianto; Asari, Hasim (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
This study was carried out due to the bureaucratic reform in terms of integrity zone implementation in State Treasury Service Office (KPPN) Pekanbaru. Since its participation in the development of integrity zone, KPPN Pekanbaru has been selected as a working unit with the predicate of Corruption Free Area (WBK) and Clean and Serving Bureaucracy (WBBM) and has become the pioneer of Integrity Zone for Riau Province. This is inseparable from the capabilities of leaders and employees of KPPN Pekanbaru. The purposes of this study were to analyze the dynamic governance capability in the development of Integrity Zone and to identify the supporting factors for the dynamic governance capability in KPPN Pekanbaru. The theoretical concepts used are the theories of dynamic governance capability by Neo and Chen, namely thinking ahead, thinking again and thinking across. This study employed a descriptive qualitative method, the data in this study were obtained from observations, interviews, literature studies and documentation. The results of the study indicated that, in the integrity zone development, leaders and employees of KPPN Pekanbaru had high capabilities, this evidence could be seen from their actions of hink ahead, think again and think across so that they have got many achievements, it was also supported by the leader’s commitment, implementation of ISO and support from the Directorate General of Treasury